Description of a new species of Ampulicomorpha Ashmead (Hymenoptera, Embolemidae) from Madagascar - Olmi, Massimo (Zootaxa, 2023)
A new species of Ampulicomorpha Ashmead, A. minima sp. nov., is described from Madagascar, Toliara Province. The female holotype is compared with the known females of all other Afrotropical species of the same genus. A new key to them is presented, together with the first complete multifocal illustration of the females of all Afrotropical species of Ampulicomorpha.